Analisis Usability Testing untuk Mengevaluasi User Interface pada Game Nowhere - Alfian Majiddan Nur; Adidarma Putra Harjun; Aynur Rofiqoh; I Putu Wedana Kartikaputra (ULIL ALBAB : Jurnal Ilmiah Multidisiplin, 2022)
The goal of this research is to analyze the UI level of the PC based game Nowhere using usability testing. The technique used is usability testing using the questioner method done by asking questions to measure user's satisfaction. The questioner is sent online to users in order to do problem analysis. Research data is received after Nowhere game's user runs the app so they can experience the game in real time. Research data samples are taken from eleven users. The data analysis method used is deductive analysis with scale from one to five then said data is described to measure the usability of the game app Nowhere.